High-Dose Vancomycin in the Treatment of Clostridioides difficile Infection: A Systematic Review and Meta-analysis. Issue 4 (3rd July 2022) - Bader, Mazen S.; Mertz, Dominik; Hawboldt, John; Farrell, Alison; Alajmi, Abdulaziz; Maleki-Yazdi, Keon
Abstract : Background: There is significant variability in guideline recommendations regarding the dosing of vancomycin in treating Clostridioides difficile infection (CDI). The aim of this systematic review and meta-analysis was to investigate the efficacy of high-dose vancomycin compared with other current standard of care and other CDI treatment regimens. Methods: We conducted a comprehensive literature search in PubMed, the Cochrane Library, Embase, and Web of Science for publications that studied the comparative effectiveness of high-dose vancomycin to other CDI treatment regimens for the period up to July 2020. Results: A total of 14 studies, 6 randomized controlled trials (372 participants) and 8 observational controlled studies (952 participants), with a total of 1324 patients were included in the final analysis. There was no statistically significant effect between high-dose vancomycin and other treatment options of CDI on clinical cure/response (odd ratio [OR], 0.70; 95% confidence interval [CI], 0.34 to 1.43; I 2 = 59%), clinical relapse and recurrence (OR, 1.01; 95% CI, 0.72–1.42; I 2 = 61%), and mortality (OR, 1.03; 95% CI, 0.37–2.84; I 2 = 44%). Conclusions: High-dose oral vancomycin was not superior to other treatment regimens for the outcomes of clinical response and cure, recurrence, and mortality of CDI.